THE USE OF PRECAST-MONOLITHIC SLABS WITH THE LOWER VAULTED SURFACE IS SLIGHTLY DEEPENED IN UNDERGROUND PEDESTRIAN CROSSINGS - A. A. Komlev; S. A. Makeev; Y. V. Krasnoshchekov (Вестник СибАДИ)
The article considers the ways of improvement of designs of overlappings slightly deepened underpasses. The proposed new design solution for precast-monolithic slabs slightly deepened underground pedestrian crossings with the lower vaulted surface is made on a permanent form of arched profiled flooring. The evaluation of the stress-strain state of beams in linear and nonlinear formulation, are compared. A comparison of technical and economic parameters of basic types of overlaps underpasses.